2018
DOI: 10.1111/febs.14419
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite accumulation in VLCAD deficiency markedly disrupts mitochondrial bioenergetics and Ca2+ homeostasis in the heart

Abstract: We studied the effects of the major long-chain fatty acids accumulating in very long-chain acyl-CoA dehydrogenase (VLCAD) deficiency, namely cis-5-tetradecenoic acid (Cis-5) and myristic acid (Myr), on important mitochondrial functions in isolated mitochondria from cardiac fibers and cardiomyocytes of juvenile rats. Cis-5 and Myr at pathological concentrations markedly reduced mitochondrial membrane potential (ΔΨ ), matrix NAD(P)H pool, Ca retention capacity, ADP- (state 3) and carbonyl cyanide 3-chlorophenyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 100 publications
1
9
0
Order By: Relevance
“…Regardless of mutation, VLCAD-deficient cells showed a marked decrease of mitochondrial RC function and ATP levels that tended to be exaggerated by growth in glucose-free media. Although the ACADVL gene mutations were heterogeneous in the examined fibroblasts, impairment in oxygen consumption was observed in all cultured cells, which is in line with observations showing that long-chain fatty acids accumulated in VLCADD impairs bioenergetics in mitochondria of rat brain (26). These findings are accompanied by increased ROS production measured with an in vivo probe and an in vitro technique.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regardless of mutation, VLCAD-deficient cells showed a marked decrease of mitochondrial RC function and ATP levels that tended to be exaggerated by growth in glucose-free media. Although the ACADVL gene mutations were heterogeneous in the examined fibroblasts, impairment in oxygen consumption was observed in all cultured cells, which is in line with observations showing that long-chain fatty acids accumulated in VLCADD impairs bioenergetics in mitochondria of rat brain (26). These findings are accompanied by increased ROS production measured with an in vivo probe and an in vitro technique.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, previous works have shown cellular toxicity induced by the major accumulated long-chain fatty acids and acylcarnitines in VLCADD. At high concentrations, these metabolites provoke mitochondrial dysfunction by different mechanisms, including calcium homeostasis disturbance, mitochondrial membrane potential dissipation, OXPHOS uncoupling and apoptosis (26,37).…”
Section: Discussionmentioning
confidence: 99%
“…Humans with very long chain acetyl-CoA dehydrogenase deficiency (VLCAD), an electron transfer flavoprotein-dependent enzyme located in the internal mitochondrial matrix, have a defect in the mitochondrial oxidation of long-chain fatty acids, leading to the development of hypertrophic heart disease and arrhythmias that can lead to death. The treatment of these patients involves the administration of glucose, a high caloric diet with medium chain triglycerides and supplementation with L-carnitine 46 . Using differentiated cardiomyocytes from pluripotent stem cells of a patient with VLCAD, it was found that resveratrol led to increased fatty acid oxidation by increasing mitochondrial biogenesis and control of cytosolic Ca 2+ concentration, which could lead to better control of arrhythmias in these patients by consuming food containing resveratrol 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Induction of mPT pore opening was also demonstrated to be caused by Myr (Bodrova et al, 2003). Recent studies demonstrated that, apart from Myr, pathological concentrations of Cis-5 disturb mitochondrial bioenergetics and calcium homeostasis in the heart, liver, and skeletal muscle (Cecatto et al, 2018a(Cecatto et al, , 2019(Cecatto et al, , 2020. These results were obtained in different tissue preparations, such as isolated mitochondria, permeabilized cardiomyocytes and hepatocytes, and heart fibers.…”
Section: Disturbance Of Mitochondrial Bioenergetics and Calcium Homeomentioning
confidence: 94%